2024
DOI: 10.3390/d16030131
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Biodiversity Conservation via Urban Ecosystem Regeneration

Gad Perry,
Robert D. Cox

Abstract: Conservation traditionally focuses on at-risk species and relatively intact ecosystems. As the human population and our global impact have risen, many more species and ecosystems are at risk and fewer intact ecosystems remain, with urbanization being a major contributing factor. Cities and their inhabitants are here to stay, and the prevalence of urbanization, often in the vicinity of areas of high conservation value, requires reconsideration of the conservation value of urban ecosystems and urban green spaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 109 publications
(196 reference statements)
0
0
0
Order By: Relevance
“…Like previous reviews, and despite the ongoing growth in relevant studies (Figure 3) and the time that has elapsed since previous reviews (e.g., [17,18]), we also found that the number of convincing demonstrations of urban evolution remains small. Also, like other assessments in a variety of context (e.g., [34], for conservation), we believe that this primarily represents a lack of city-based research effort rather than a lack of opportunity for research or a lack of urban evolutionary events. There is an apparent bias in the biological fields against urban studies [48,[197][198][199], though bird species found in multiple cities are more frequently studied [200].…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Like previous reviews, and despite the ongoing growth in relevant studies (Figure 3) and the time that has elapsed since previous reviews (e.g., [17,18]), we also found that the number of convincing demonstrations of urban evolution remains small. Also, like other assessments in a variety of context (e.g., [34], for conservation), we believe that this primarily represents a lack of city-based research effort rather than a lack of opportunity for research or a lack of urban evolutionary events. There is an apparent bias in the biological fields against urban studies [48,[197][198][199], though bird species found in multiple cities are more frequently studied [200].…”
Section: Discussionmentioning
confidence: 74%
“…Urbanization thus creates a new biological milieu for species, for example by removing predators they coevolved with, adding unfamiliar competitors, or forcing changes to migration patterns [33]. While the urbanization process was previously viewed almost exclusively as a threat scenario for biological diversity, this perception is changing and the ecological value of urban habitats is increasingly coming into focus (e.g., [34]). Overall, however, the effects of urbanization extend beyond the city limit, for example, through agricultural efforts in support of human nutrition in the urbanized areas [16].…”
Section: Urbanization As An Ecological Phenomenon and A Conservation ...mentioning
confidence: 99%
See 2 more Smart Citations